Evaluation of Antibacterial and Antibiofilm Properties of Phenolics with Coumarin, Naphthoquinone and Pyranone Moieties Against Foodborne Microorganisms - Alejandra Alejo-Armijo; Antonio Cobo; Alfonso Alejo-Armijo; Joaquín Altarejos; Sofía Salido; Elena Ortega-Morente (Molecules)
Numerous studies have previously demonstrated the antimicrobial activity of plant extracts rich in procyanidins. However, these investigations that focused on uncharacterized extracts do not provide information on the structure–activity relationships of these compounds. The aim of this work was to investigate the antibacterial and antibiofilm properties of 27 phenolics with coumarin, naphthoquinone and pyranone moieties against foodborne microorganisms, as well as to establish structure–activity relationships. Minimal inhibitory concentrations (MICs) for each compound were investigated, as well as their ability for inhibiting biofilm formation as well as disrupting previously formed biofilms by food pathogens. Our compounds show high antibacterial and antibiofilm activities against Gram-positive bacteria. Regarding the structure–activity relationships observed, the coumarin moiety seems to favor the antibacterial activity against both S. aureus strains assayed, while a naphthoquinone moiety enhances antibacterial effects against B. cereus. Moreover, the replacement of OH groups in the B-ring by methoxy groups impairs antibacterial activity of the compounds against target bacteria, while the presence of Cl or OH groups in the molecules seems to enhance the inhibition of biofilm formation as well as the disruption of preformed biofilms. These results may be of great relevance for the food sector, increasing the options of additives that can be used industrially.